Comparison of the Effectiveness of Immersion Curing and Burlap Sacks Curing on the Compressive Strength of Concrete with Superplasticizers - Darayani, Dhiafah Hera; Juanita; Hafiz Hamdani; Cindrawati (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2026)
This study aims to examine the effectiveness of two concrete treatment methods with SikaCim superplasticizer on concrete compressive strength. The curing method was used by immersion in water and covering the concrete surface with wet gunny sacks. The compressive strength test was conducted when the concrete was 28 days old. The concrete used is normal concrete and normal concrete with additives. This study tested concrete with 24 cylindrical specimens (15 cm x 30 cm). The results of the concrete compressive strength study show that the values of normal concrete soaked in water, with normal concrete covered with burlap sacks shows an increase of 30.6%. For comparison, the concrete treatment of added superplasticizer soaked in water, with the concrete added superplasticizer covered with burlap sacks, increased by 25.4%. The conclusion is that the highest compressive strength occurs in concrete with superplasticizer additives, with treatment covered with wet burlap sacks, which is 25.57 MPa.